The significance of linkages with foreign universities in the advertisements of local institutions of higher education / Mohd Ridzuan Nordin, Lim Yet Mee and Lim Kwee Pheng - Nordin, Mohd Ridzuan; Lim, Yet Mee; Lim, Kwee Pheng (2002)
The linkages with foreign universities featured prominently in the advertisements of local institutions of higher education. The 3+0 colleges were observed to capitalise on these links more extensively than the normal colleges. As a result the 3+0 colleges were able to perform best in comparison to the normal colleges and the private universities. This indicates that the links with foreign universities serve as a major attraction for the colleges. The private universities advertise least and do not project the links with foreign universities prominently. Nevertheless the universities obtained the largest revenue per institution. This indicates that the service offered by the universities is differentiated from that offered by the colleges. The Malaysian public seems to be more receptive to service offered by the private universities than that of the colleges. Based on the findings of this study, it is proposed that private universities require different marketing mix than that for colleges. In this marketing mix, private universities can have lesser advertisements than that for the colleges. As for the colleges, clearer and more frequent advertising helps to increase revenue. On the other hand the public have a clearer knowledge about private universities. This is probably a result of the higher quality image of universities than that of colleges. A marketing mix that reinforces this image would be advantageous for the universities. This may entails using advertisement to inform the public on new intake and new programmes and resorting to publicity and promotion to project and maintain the quality image and high achievements of the universities.